DEVELOPMENT OF A GREEN ECONOMIC MODEL FOR TOURISM VILLAGES IN SUBANG: A NATURAL RESOURCE-BASED VALUE APPROACH AND SYSTEMS THINKING METHODOLOGY - Ratih Ayu Sekarini; Wiwin; Hilma Farhani; Rita Siti Fatimah (RADJA PUBLIKA, 2026)
This study aims to develop a green economy model in Cisaat Tourism Village through the Natural Resource Based Value (NRBV) and Systems Thinking Methodology approaches. The study uses a mixed methods approach by combining semi-structured interviews with 3 village officials, 5 business actors, and 3 community leaders, as well as a quantitative survey of 50 respondents using probability sampling techniques. The NRBV approach is used to assess the intrinsic value of natural resources, while systems thinking analyses the interrelationships between environmental, social, and economic aspects in a sustainable tourism system. The results of the study show that the development of Cisaat Tourism Village still faces major obstacles in the form of a weak village identity, the impact of study tour restrictions on tourist visits, weak digital promotion, and limited seasonal culinary ingredients. Theoretically, this study emphasises the importance of integrating village identity, policy adaptation, digitalisation of promotion, and culinary innovation in the development of green economy-based tourism.